Effect of the water absorptive capacity of reinforcing fibers on the process ability, morphology, and performance characteristics of composites produced from polyfurfuryl alcohol - Katharina Resch-Fauster (Advanced Manufacturing: Polymer & Composites Science, 2018)
Some matrix polymers, such as polyfurfuryl alcohol (PFA) generate water during the processing of fiber-reinforced polymer composites which slows down the process speed and may adversely affect the overall material properties. In this paper, the effect of the water absorbance characteristics of reinforcing fibers on the process ability of PFA composites at short cycle times (industrial processing) is investigated and evaluated. Natural and synthetic fiber types which exhibit a high, medium, and low water absorbance capacity as well as different textile architectures are compared. The processing-induced composite morphology is assessed and correlated with the material’s mechanical properties. The results reveal a high potential of hydrophilic natural fibers for significantly reducing the processing time while maintaining the overall performance characteristics of PFA composites.